Climate Mitigation in Urban Planning using Scenario Analysis - Narezhnaya Tamara; Rajasekhar Boddu; Singarapu Satish; Singh Takveer; John Vivek; Khurana Preeti; Jagga Megha; Kumar Yogesh; Hussein Ramy Riad (E3S Web of Conferences)
This study investigates climate mitigation solutions in urban planning using a thorough scenario analysis methodology. This research seeks to find actionable insights for sustainable development by evaluating production indicators, resource use, process efficiency, and cost management in urban settings. The investigation examines a four-month period, uncovering notable trends in resource distribution and Urban Planning. February had the greatest implementation of sustainable measures, corresponding with a decrease in environmental effect indices. The research identifies an ideal resource utilization rate of eighty percent for urban infrastructure, effectively reconciling operational requirements with financial limitations. The research reveals that the planning and implementation stages are often efficient, however it underscores significant prospects for improvement in community participation and policy integration. This study highlights the need of integrating urban development with climate objectives, directing stakeholders towards comprehensive policies that promote enduring sustainability and resilience in urban ecosystems.